Recommendations for creating a trust infrastructure in the interests of the digital ruble system - Melnikov, Dmitry A.; Budnikov, Dmitry A.; Konnova, Irina G.; Kubaev, Alexander V. (Bezopasnostʹ informat͡s︡ionnykh tekhnologiĭ, 2024)
Problem description. One of the areas of digital transformation of Russian society is the development and implementation of the National Digital Ruble System (DR) in the credit and financial sphere (CFS) of the economy of the Russian Federation. The National DR system should be based on the information technology infrastructure (ITI) for ensuring information security (IS). In fact, the ITI for ensuring IS is a trust infrastructure (ITIT) based on the public key infrastructure (PKI). ITIT should have a number of functional properties, including identification and authentication of objects and subjects of electronic financial transactions, protection of the integrity and confidentiality of data and the electronic financial transactions themselves, implementation of the principle of non-repudiation of the parties to information interaction. At the same time, the absence of ITIT in the National DR System can completely discredit the very idea of digitalization of the CFS, associated with the absence of any guarantees of reliability and trust in the National DR System, based on the implementation of the entire range of methods and means of cryptographic protection of information (electronic financial transactions), including systems for managing cryptographic keys. The absence of comprehensive protection of the National DR System will entail risks and problems in ensuring IS, which can negatively affect individuals, groups, organizations, sectors of the economy and society as a whole. Goals. To propose and analyze a heuristic model of DR and a model of functional and structural ITIT, which solves the main problems of ensuring IS of the National DR System, associated primarily with confirmation of the authenticity and ownership of DR, as well as the protection of electronic payment transactions and the possibility of withdrawing (withdrawing from circulation) DR immediately (on-line) after detection of its compromise. Results. The article presents a heuristic (hypothetical) model of C₽ and describes the DR format (as an information object) that includes cryptographically linked information blocks and public key certificates issued by accredited certification authorities using electronic signatures. A functional and structural model of the ITIT of the National DR System is proposed. The composition, main elements of the ITIT structure, as well as their goals and implemented functions are described. The results of the analysis of trust assurance based on the PKI of the Bank of Russia (BR) are presented. Practical significance. The heuristic (hypothetical) model of DR, the functional and structural model of the ITIT of the National DR System and the results of the analysis of trust assurance based on the PKI of the BR are of great practical significance in the development and implementation of the National DR System in the CFS of the Russian Federation economy. Conclusions. The results obtained will increase the level of security and trust in the National DR System of the citizens, businesses and credit and financial institutions.